Prevalence of Frailty Among Thai Elderly Under Universal Health Coverage at a University Tertiary Hospital Residing in Nakhon Nayok Province - Charoensuksiri, Siripich; Suttinak, Supanan; Charoensuksiri, Khemmapak (Ramathibodi Medical Journal, 2025)
Background: Frailty is a major health issue among Thai elderly individuals. This condition increases the risk of illness and injuries from falls. Objective: To study the prevalence of frailty among Thai elderly residing in Nakhon Nayok province. Methods: This descriptive cross-sectional study included elderly Thai individuals residing in Nakhon Nayok province, using a purposive sampling method. The research instruments consisted of a demographic data questionnaire and the Thai version of the Simple Frailty Questionnaire. The data were analyzed using descriptive statistics. Results: The total sample consisted of 353 volunteers aged 60-96 years, 54.94% of whom were female. The most common underlying disease was hypertension. Most participants could continue activities for more than 30 minutes, and 8.22% reported a history of falls, primarily due to slipping. The most common consequence of falling was abrasions. The prevalence of frailty in this study was found to be 9.06%, predominantly among females aged 70-79 years. Conclusions: The study is beneficial for healthcare professionals, as they can use the information to monitor changes in frailty in their area, manage health promotion with a focus on frailty prevention, and plan health services appropriately for actual health conditions.